-4p-2p+8p-15+3=

Simple and best practice solution for -4p-2p+8p-15+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4p-2p+8p-15+3= equation:


Simplifying
-4p + -2p + 8p + -15 + 3 = 0

Reorder the terms:
-15 + 3 + -4p + -2p + 8p = 0

Combine like terms: -15 + 3 = -12
-12 + -4p + -2p + 8p = 0

Combine like terms: -4p + -2p = -6p
-12 + -6p + 8p = 0

Combine like terms: -6p + 8p = 2p
-12 + 2p = 0

Solving
-12 + 2p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 2p = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 2p = 0 + 12
2p = 0 + 12

Combine like terms: 0 + 12 = 12
2p = 12

Divide each side by '2'.
p = 6

Simplifying
p = 6

See similar equations:

| 9(d+2)=3(d-2) | | -6(-x-7)=90 | | 1128/(-47)= | | 3x+5x=2(4+7) | | -2x-4(0.25+0.5x)=1 | | 15p+7q+5p-4q= | | (1-7i)-(1-5i)= | | 5t-3=7 | | X/18+1=-3 | | (a^8b^2)(a^6b^8)= | | 4x-6x=x-9 | | b=85+(10+7)w | | 10x/5x-1=5+2/5x-1 | | 7x-(-4)=54 | | 7(r-1)-3=2r+5 | | -7(n+7)=4n-16 | | 4x+9-x= | | ln(4-2x)+ln(9-3x)=21n(x+1) | | 2(9x+5)=-26 | | 3z+1/4=4z+7/4 | | 86=-70+13x | | 2b+4028=51514 | | 17+-5= | | -2(4x+2)=12 | | 5x-x+2=2x+2x+2 | | 2(2x+30)+4x=360 | | (2-4i)+(1-4i)= | | 0=x^2-1 | | 11b-2b= | | 13+(-6n)+(-15)+(-5n)= | | 1.1x+-5.4=-10 | | 5/9x=5/3 |

Equations solver categories